A Local Study on Antenatal Features of Preterm Births at 26-32 Versus 33-36 Weeks of Pregnancy - Fusun Varol; Nuray Er; Necdet Sut; Cenk N. Sayin (Medical Network, 2018)
Objective: The antenatal features of pregnancies affect the incidence of preterm births. This retrospective study from Trakya University of Northwestern Turkey, describes antenatal factors involved in preterm births at 26-32 weeks of pregnancy and compares with those involved in preterm births at 33-36 weeks. Study Design: The records of preterm births at 26-32 weeks (earlier preterm births, n=419) and at 33-36 weeks (later preterm births, n=158) during the years 2002-2010 were reviewed and the demographic, obstetric and medical features were evaluated retrospectively. The data was expressed as numbers and percentages and analyzed by SPSS 20.0. Results: Iron supplementation [OR 0.27 (0.16-0.45), p=<0.001], short cervix [OR 9.12 (2.09-39.73) p=0.003] and infection [OR 2.6 (1.2-5.6) p=0.014] were important factors in the emergence of earlier preterm births which occurred at the rate of 1.4%. Conclusions: Earlier preterm births at 26-32 weeks of pregnancy, which compose an obstetric issue, are associated with several antenatal risk factors such as nutrition, cervical problems and infections in Northwestern Turkey.